Pelaksanaan Mediasi dalam Penanganan Cerai Gugat di Pengadilan Agama Pekanbaru - Mardalena Hanifah; Rahma Sari; Jennie Qothrunnada Kurnia (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the implementation of mediation in divorce lawsuits at Religious Court of Pekanbaru as an effort to resolve disputes peacefully. This empirical legal research employs a sociological approach through interviews, observations and literature studies. The results show that mediation has been conducted in accordance with procedures; however, its success rate remains low due to legal uncertainty, limited facilities, conflict complexity, the psychological condition of the parties and the legal culture of society that views divorce as the final solution.